Calibration of Local Systems with Lyophilized Calibrant Plasmas Improves the Interlaboratory Variability of the INR in the Italian External Quality Assessment Scheme - Chantarangkul, Veena; Tripodi, Armando; Cesana, Bruno M.; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1999)
Calibration with lyophilized calibrant plasmas certified in terms of PT with International Reference Preparations for thromboplastin has been proposed to minimize the effect of coagulometers on the INR. Aim of this study was to test the ability of local calibration with lyophilized calibrant plasmas, combined with a modified statistical approach, to improve the interlaboratory variability of the INR measured on two test plasmas (one coumarin and one artificially-depleted) by participants in the External Quality Assessment Scheme (EQAS). Sets of lyophilized calibrant and test plasmas were sent to the participants in the EQAS, who were asked to determine PT with their own reagent/ instrument combination (local system). Results were returned as PT together with information on the type of local system, the stated International Sensitivity Index (ISI) and the geometric mean of PTs determined by testing with the local system fresh plasmas from 20 healthy subjects. Ninety-two participants using 9 and 11 brands of reagents and instruments returned results. The CV of the INR determined with the stated ISI for the coumarin (Mean INR = 4.39) and artificially-depleted (Mean INR = 4.23) test plasmas were 11.2% and 10.3% and were reduced on the average by 34% and 54%, respectively, when the INR was calculated with the local ISI.In conclusions, results from this field study involving laboratories and testing systems representative of the real situation in oral anticoagulant monitoring in our country, indicate that local calibration by artificially-depleted plasmas, combined with the proposed statistical approach, is suitable to improve the interlaboratory agreement on the INR.
Keywords: INR; standardization; anticoagulant therapy; lyophilized plasmas